Herkunftsbedingte und sprachliche Einflüsse bei der häuslichen Internetnutzung von Kindern - Richter, Lea; Gruchel, Nicole; Buhl, Heike M.; Kamin, Anna-Maria (MedienPädagogik: Zeitschrift für Theorie und Praxis der Medienbildung)
Der Beitrag betrachtet die digitale häusliche Lernumwelt von Kindern unter besonderer Berücksichtigung der Differenzkategorien Herkunft und Sprache und erarbeitet Zusammenhänge zwischen dem Migrationshintergrund, der Familiensprache, einer internetbezogenen Eltern-Kind-Interaktion sowie einer unterhaltungs- und schulbezogenen Nutzung des Internets von Kindern. Empirische Grundlagen sind standardisierte Eltern- und Kinderbefragungen sowie ethnografisch orientierte Untersuchungen in Familien. Die quantitativen Analysen zeigen, dass Kinder, deren Hauptverkehrssprache in der Familie nicht Deutsch ist, häufiger gemeinsam mit ihren Eltern das Internet nutzten. Vertiefend liessen in der qualitativen Untersuchung diejenigen Kinder häufigere und komplexere Internetnutzungsformen für schulische Zwecke erkennen, die einen Migrationshintergrund aufweisen und hauptsächlich in ihrer Herkunftssprache (nicht Deutsch) innerhalb der Familie sprechen. Insbesondere in Familien, die selten in der Häuslichkeit Deutsch sprechen, hat sich die (gemeinsame) Internetrecherche als Mittel zur Kompensation von Sprachbarrieren erwiesen. Fehlende elterliche Unterstützungsmöglichkeiten aufgrund von sprachlichen Verständnisproblemen können insofern durch kindliche, elterliche oder gemeinsame Rechercheprozesse ausgeglichen werden.

A PRACTICAL HANDBOOK ON EFFECTIVE DEVELOPMENT AND IMPLEMENTATION OF STEAM TEACHING AT SCHOOL

Inclusion and the Development of Technology Education - Thinking towards an inclusive curriculum for technology education in German primary schools - Schröer, Franz; Tenberge, Claudia (Bloomsbury Handbook of Technology Education.)

Impact of 3D Curvature on the Polarization Orientation in Non-Ising Domain Walls - Acevedo-Salas, Ulises; Croes, Boris; Zhang, Yide; Cregut, Olivier; Dorkenoo, Kokou Dodzi; Kirbus, Benjamin; Singh, Ekta; Beccard, Henrik; Rüsing, Michael; Eng, Lukas M.; Hertel, Riccardo; Eliseev, Eugene A.; et al. (Nano Letters)
Ferroelectric domain boundaries are quasi-two-dimensional functional interfaces with high prospects for nanoelectronic applications. Despite their reduced dimensionality, they can exhibit complex non-Ising polarization configurations and unexpected physical properties. Here, the impact of the three-dimensional (3D) curvature on the polarization profile of nominally uncharged 180° domain walls in LiNbO3 is studied using second-harmonic generation microscopy and 3D polarimetry analysis. Correlations between the domain-wall curvature and the variation of its internal polarization unfold in the form of modulations of the Néel-like character, which we attribute to the flexoelectric effect. While the Néel-like character originates mainly from the tilting of the domain wall, the internal polarization adjusts its orientation due to the synergetic upshot of dipolar and monopolar bound charges and their variation with the 3D curvature. Our results show that curved interfaces in solid crystals may offer a rich playground for tailoring nanoscale polar states.
Keywords: Mechanical Engineering; Condensed Matter Physics; General Materials Science; General Chemistry; Bioengineering

Vibrational properties of LiNbO3 and LiTaO3 under uniaxial stress - Singh, Ekta; Pionteck, Mike N.; Reitzig, Sven; Lange, Michael; Rüsing, Michael; Eng, Lukas M.; Sanna, Simone (Physical Review Materials)
Structural strain severely impacts material properties, such as the linear and nonlinear optical response. Moreover, strain plays a key role, e.g., in the physics of ferroelectrics and, in particular, of their domain walls. μ-Raman spectroscopy is a well-suited technique for the investigation of such strain effects as it allows to measure the lattice dynamics locally. However, quantifying and reconstructing strain fields from Raman maps requires knowledge on the strain dependence of phonon frequencies. In this paper, we have analyzed both theoretically and experimentally the phonon frequencies in the widely used ferroelectrics lithium niobate and lithium tantalate as a function of uniaxial strain via density functional theory and μ-Raman spectroscopy. Overall, we find a good agreement between our ab initio models and the experimental data performed with a stress cell. The majority of phonons show an increase in frequency under compressive strain, whereas the opposite is observed for tensile strains. Moreover, for E-type phonons, we observe the lifting of degeneracy already at moderate strain fields (i.e., at ±0.2%) along the x and y directions. This paper, hence, allows for the systematic analysis of three-dimensional strains in modern-type bulk and thin-film devices assembled from lithium niobate and tantalate.
Keywords: Physics and Astronomy (miscellaneous); General Materials Science

Modeling nonlinear optical interactions of focused beams in bulk crystals and thin films: A phenomenological approach - Spychala, Kai J.; Amber, Zeeshan H.; Eng, Lukas M.; Rüsing, Michael (Journal of Applied Physics)
Coherent nonlinear optical μ-spectroscopy is a frequently used tool in modern material science as it is sensitive to many different local observables, which comprise, among others, crystal symmetry and vibrational properties. The richness in information, however, may come with challenges in data interpretation, as one has to disentangle the many different effects like multiple reflections, phase jumps at interfaces, or the influence of the Guoy-phase. In order to facilitate interpretation, the work presented here proposes an easy-to-use semi-analytical modeling Ansatz, which bases upon known analytical solutions using Gaussian beams. Specifically, we apply this Ansatz to compute nonlinear optical responses of (thin film) optical materials. We try to conserve the meaning of intuitive parameters like the Gouy-phase and the nonlinear coherent interaction length. In particular, the concept of coherence length is extended, which is a must when using focal beams. The model is subsequently applied to exemplary cases of second- and third-harmonic generation. We observe a very good agreement with experimental data, and furthermore, despite the constraints and limits of the analytical Ansatz, our model performs similarly well as when using more rigorous simulations. However, it outperforms the latter in terms of computational power, requiring more than three orders less computational time and less performant computer systems.
Keywords: General Physics and Astronomy

Thermophoretic Analysis of Biomolecules across the Nanoscales in Self-Assembled Polymeric Matrices - Liu, Ping; Schumann, Nils; Abele, Fabian; Ren, Fazheng; Hanke, Marcel; Xin, Yang; Hartmann, Andreas; Schlierf, Michael; Keller, Adrian; Lin, Weilin; Zhang, Yixin (ACS Applied Nano Materials)
Keywords: General Materials Science

Fünf Thesen zur Untersuchung des Textsortenwandels - Schuster, Britt-Marie; Haaf, Susanne (Historische Textmuster im Wandel. Neue Wege zu Ihrer Erschließung)

Fragen stellen in Pressetextsorten - Schuster, Britt-Marie; Thielert, Frauke; Haaf, Susanne (Historische Textmuster im Wandel. Neue Wege zu ihrer Erschließung)

»Das dankst du deinem Führer« – Adressierungspraktiken in der Widerstandskommunikation gegen den Nationalsozialismus - Schuster, Britt-Marie (Kommunikative Praktiken im Nationalsozialismus)
Keywords: Kommunikationsgeschichte

Widerstandshandeln. Sprachliche Praktiken des Sich-Widersetzens zwischen 1933 und 1945

»Viele alte Aufgaben wurden damit in einem neuen Lichte gesehen« - Gretz, Daniela (Deutsche Vierteljahrsschrift für Literaturwissenschaft und Geistesgeschichte)
Zusammenfassung Dieser Beitrag widmet sich dem Zusammenhang von geistesgeschichtlicher Literaturgeschichtsschreibung und dem Konzept der ›deutschen Bewegung‹. Er rekonstruiert vor allem dessen germanistische Adaption und Weiterentwicklung durch Paul Kluckhohn sowie seinen polyvalenten Einsatz zum heft- und jahrgangsübergreifenden Erzählen einer fortgesetzten nationalen Geistesgeschichte in der Deutschen Vierteljahrsschrift .
Keywords: Literature and Literary Theory; Philosophy; Cultural Studies

Stakeholder-oriented Elaboration of Artificial Intelligence use cases using the example of Special-Purpose engineering - Humpert, Lynn; Wäschle, Moritz; Horstmeyer, Sarah; Anacker, Harald; Dumitrescu, Roman; Albers, Albert (Procedia CIRP)
Keywords: General Medicine

Performance and Usability Evaluation of Brainwave Authentication Techniques with Consumer Devices - Arias-Cabarcos, Patricia; Fallahi, Matin; Habrich, Thilo; Schulze, Karen; Becker, Christian; Strufe, Thorsten (ACM Transactions on Privacy and Security)
Brainwaves have demonstrated to be unique enough across individuals to be useful as biometrics. They also provide promising advantages over traditional means of authentication, such as resistance to external observability, revocability, and intrinsic liveness detection. However, most of the research so far has been conducted with expensive, bulky, medical-grade helmets, which offer limited applicability for everyday usage. With the aim to bring brainwave authentication and its benefits closer to real world deployment, we investigate brain biometrics with consumer devices. We conduct a comprehensive measurement experiment and user study that compare five authentication tasks on a user sample up to 10 times larger than those from previous studies, introducing three novel techniques based on cognitive semantic processing. Furthermore, we apply our analysis on high-quality open brainwave data obtained with a medical-grade headset, to assess the differences. We investigate both the performance, security, and usability of the different options and use this evidence to elicit design and research recommendations. Our results show that it is possible to achieve Equal Error Rates as low as 7.2% (a reduction between 68–72% with respect to existing approaches) based on brain responses to images with current inexpensive technology. We show that the common practice of testing authentication systems only with known attacker data is unrealistic and may lead to overly optimistic evaluations. With regard to adoption, users call for simpler devices, faster authentication, and better privacy.
Keywords: Safety; Risk; Reliability and Quality; General Computer Science

'Surprised, Shocked, Worried'}: User Reactions to Facebook Data Collection from Third Parties - Arias-Cabarcos, Patricia; Khalili, Saina; Strufe, Thorsten (Proceedings on Privacy Enhancing Technologies)
Data collection and aggregation by online services happens to an extent that is often beyond awareness and comprehension of its users. Transparency tools become crucial to inform people, though it is unclear how well they work. To investigate this matter, we conducted a user study focusing on Facebook, which has recently released the 'Off-Facebook Activity' transparency dashboard that informs about personal data collection from third parties. We exposed a group of n = 100 participants to the dashboard and surveyed their level of awareness and reactions to understand how transparency impacts users' privacy attitudes and intended behavior. Our participants were surprised about the massive amount of collected data, became significantly less comfortable with data collection, and more likely to take protective measures. Collaterally, we observed that current consent schemes are inadequate. Based on the survey findings, we make recommendations for more usable transparency and highlight the need to raise awareness about transparency tools and to provide easily actionable privacy controls.
Keywords: General Medicine

Pseudo-Labeling Machine Learning Algorithm for Predictive Maintenance of Relays - Winkel, Fabian; Wallscheid, Oliver; Scholz, Peter; Böcker, Joachim (IEEE Open Journal of the Industrial Electronics Society)
Keywords: Electrical and Electronic Engineering; Industrial and Manufacturing Engineering; Control and Systems Engineering

Run-to-Failure Relay Dataset for Predictive Maintenance Research With Machine Learning - Winkel, Fabian; Deuse-Kleinsteuber, Johannes; Böcker, Joachim (IEEE Transactions on Reliability)
Keywords: Electrical and Electronic Engineering; Safety; Risk; Reliability and Quality

BrainNet: Improving Brainwave-based Biometric Recognition with Siamese Networks - Fallahi, Matin; Strufe, Thorsten; Arias-Cabarcos, Patricia (2023 IEEE International Conference on Pervasive Computing and Communications (PerCom))

Neural Networks as Black-Box Benchmark Functions Optimized for Exploratory Landscape Features - Prager, Raphael Patrick; Dietrich, Konstantin; Schneider, Lennart; Schäpermeier, Lennart; Bischl, Bernd; Kerschke, Pascal; Trautmann, Heike; Mersmann, Olaf (Proceedings of the 17th ACM/SIGEVO Conference on Foundations of Genetic Algorithms)
Artificial benchmark functions are commonly used in optimization research because of their ability to rapidly evaluate potential solutions, making them a preferred substitute for real-world problems. However, these benchmark functions have faced criticism for their limited resemblance to real-world problems. In response, recent research has focused on automatically generating new benchmark functions for areas where established test suites are inadequate. These approaches have limitations, such as the difficulty of generating new benchmark functions that exhibit exploratory landscape analysis (ELA) features beyond those of existing benchmarks.The objective of this work is to develop a method for generating benchmark functions for single-objective continuous optimization with user-specified structural properties. Specifically, we aim to demonstrate a proof of concept for a method that uses an ELA feature vector to specify these properties in advance. To achieve this, we begin by generating a random sample of decision space variables and objective values. We then adjust the objective values using CMA-ES until the corresponding features of our new problem match the predefined ELA features within a specified threshold. By iteratively transforming the landscape in this way, we ensure that the resulting function exhibits the desired properties. To create the final function, we use the resulting point cloud as training data for a simple neural network that produces a function exhibiting the target ELA features. We demonstrate the effectiveness of this approach by replicating the existing functions of the well-known BBOB suite and creating new functions with ELA feature values that are not present in BBOB.
Keywords: Benchmarking; Instance Generator; Black-Box Continuous Optimization; Exploratory Landscape Analysis; Neural Networks

Nullifying the Inherent Bias of Non-invariant Exploratory Landscape Analysis Features - Prager, Raphael Patrick; Trautmann, Heike (Applications of Evolutionary Computation)
Exploratory landscape analysis (ELA) in single-objective black-box optimization relies on a comprehensive and large set of numerical features characterizing problem instances. Those foster problem understanding and serve as basis for constructing automated algorithm selection models choosing the best suited algorithm for a problem at hand based on the aforementioned features computed prior to optimization. This work specifically points to the sensitivity of a substantial proportion of these features to absolute objective values, i.e., we observe a lack of shift and scale invariance. We show that this unfortunately induces bias within automated algorithm selection models, an overfitting to specific benchmark problem sets used for training and thereby hinders generalization capabilities to unseen problems. We tackle these issues by presenting an appropriate objective normalization to be used prior to ELA feature computation and empirically illustrate the respective effectiveness focusing on the BBOB benchmark set.

Peak-A-Boo! Generating Multi-objective Multiple Peaks Benchmark Problems with Precise Pareto Sets - Schäpermeier, Lennart; Kerschke, Pascal; Grimme, Christian; Trautmann, Heike (Evolutionary Multi-Criterion Optimization)
The design and choice of benchmark suites are ongoing topics of discussion in the multi-objective optimization community. Some suites provide a good understanding of their Pareto sets and fronts, such as the well-known DTLZ and ZDT problems. However, they lack diversity in their landscape properties and do not provide a mechanism for creating multiple distinct problem instances. Other suites, like bi-objective BBOB, possess diverse and challenging landscape properties, but their optima are not well understood and can only be approximated empirically without any guarantees.

Pflacco: Feature-Based Landscape Analysis of Continuous and Constrained Optimization Problems in Python - Prager, Raphael Patrick; Trautmann, Heike (Evolutionary Computation)
The herein proposed Python package pflacco provides a set of numerical features to characterize single-objective continuous and constrained optimization problems. Thereby, pflacco addresses two major challenges in the area optimization. Firstly, it provides the means to develop an understanding of a given problem instance, which is crucial for designing, selecting, or configuring optimization algorithms in general. Secondly, these numerical features can be utilized in the research streams of automated algorithm selection and configuration. While the majority of these landscape features is already available in the R package flacco, our Python implementation offers these tools to an even wider audience and thereby promotes research interests and novel avenues in the area of optimization.

K-12 Data Science Education: Outcomes of a National Workshop; International Perspectives; and Next Steps for the Learning Sciences - Wilkerson, Michelle; Ben-Zvi, Dani; Dvir, Michal; Matuk, Camilla; Podworny, Susanne; Stephens, Amy; Zapata-Cardona, Lucia (General Proceedings of the ISLS Annual Meeting: Building Knowledge and Sustaining our Community)

Statistics and Probability Education in Germany - Podworny, Susanne (Advances in Mathematics Education)

Tax Morale and the Church: How Catholic Clergies Adapted Norms of Paying Taxes to Secular Institutions (1940s–1950s) - Schönhärl, Korinna (Reassessing the Moral Economy Religion and Economic Ethics from Ancient Greece to the 20th Century)
Paying taxes is a field of economic activity that has always been highly morally charged: the question of who pays how much or can avoid or evade the prescribed payments is always closely related to debate about a fair societal distribution of burdens. In the process of moralisation, therefore, faith communities such as the Catholic Church also repeatedly seized the floor to propagate certain norms. The article examines the contributions of theologians from Spain, the USA and West Germany in the 1940s and 1950s. It concludes that the norms of taxation they propagated differed greatly depending on the institutional and economic frameworks within which they operated. The analysis proves taxation to be a field of economic action and societal dispute where economics and morality are indissolubly interconnected.
Keywords: Tax history; religious history: financial history; catholic church; history of economic thought

Bildungsforschung – Erziehungswissenschaftliche Perspektiven

Correlation between SLS-Powder processability and particle properties - Rüther, Moritz Johannes; Klippstein, Sven Helge; Schmid, Hans-Joachim (PARTEC International Congress on Particle Technology - Book of Abstracts)

Vergleichskonstruktionen im Mittelniederdeutschen - Wallmeier, Nadine; Wich-Reif, Claudia (Historische (Morpho-)Syntax des Deutschen)

Sarah Ihnen (2000): Relativsätze im Mittelniederdeutschen. Korpuslinguistische Untersuchungen zu Struktur und Gebrauch. - Wallmeier, Nadine (Linguistische Berichte)

Hybrid renewable energy utility systems for industrial sites: A review - Walmsley, Timothy Gordon; Philipp, Matthias; Picón-Núñez, Martín; Meschede, Henning; Taylor, Matthew Thomas; Schlosser, Florian; Atkins, Martin John (Renewable and Sustainable Energy Reviews)
Keywords: Renewable Energy; Sustainability and the Environment

Regierende Herrscherwitwen und die Angst vor Fremdherrschaft. Zum Verhältnis von Dynastie und Geschlecht - Foerster, Anne (Regentinnen und andere Stellvertreterfiguren Vom 10. bis zum 15. Jahrhundert)

Die Stimmen der Eroberten bei Ermoldus Nigellus. Eine Mahnung an Ludwig den Frommen und Pippin von Aquitanien - Foerster, Anne (Eroberte im Mittelalter: Umbruchssituationen erleben, bewältigen, gestalten)

To share or not to share: What risks would laypeople accept to give sensitive data to differentially-private NLP systems?

Privacy-Preserving Natural Language Processing - Habernal, Ivan; Mireshghallah, Fatemehsadat; Thaine, Patricia; Ghanavati, Sepideh; Feyisetan, Oluwaseyi (Proceedings of the 17th Conference of the European Chapter of the Association for Computational Linguistics: Tutorial Abstracts)

Trade-Offs Between Fairness and Privacy in Language Modeling - Matzken, Cleo; Eger, Steffen; Habernal, Ivan (Findings of the Association for Computational Linguistics: ACL 2023)

Crowdsourcing on Sensitive Data with Privacy-Preserving Text Rewriting - Mouhammad, Nina; Daxenberger, Johannes; Schiller, Benjamin; Habernal, Ivan (Proceedings of the 17th Linguistic Annotation Workshop (LAW-XVII))

Privacy-Preserving Models for Legal Natural Language Processing - Yin, Ying; Habernal, Ivan (Proceedings of the Natural Legal Language Processing Workshop 2022)

Text-Bild-Bezüge in illustrierten Flugblättern von 1500 bis 1700 - Wille, Manuel (Text und Bild: Relationen und Funktionen in Texten vom 8. bis 18. Jahrhundert : Akten zum internationalen Kongress 17. bis 19. Juni 2021)

An Optimized Third-Harmonic Injection Reduces DC-Link Voltage Ripple in Cascaded H-Bridge Converters up to 50% for all Power Factors - Unruh, Roland; Böcker, Joachim; Schafmeister, Frank (2023 25th European Conference on Power Electronics and Applications (EPE'23 ECCE Europe))
Star-connected cascaded H-bridge Converters require large DC-link capacitors to buffer the second-order harmonic voltage ripple. First, it is analytically proven that the DC-link voltage ripple is proportional to the apparent converter power and does not depend on the power factor for nominal operation with sinusoidal reference arm voltages and currents. A third-harmonic zero-sequence voltage injection with an optimal amplitude and phase angle transforms the 2nd harmonic to a 4th harmonic DC-link voltage ripple. This reduces the voltage ripple by exactly 50% for all power factors at steady-state at balanced conditions. However, this requires 54% additional modules for unity power factor operation and even 100% for pure reactive power operation to account for the increased reference arm voltages due to the large amplitude of the optimal third-harmonic injection. If not enough modules are available, an adaptive discontinuous PWM is utilized to still minimize the voltage ripple for the given number of modules and power factor. With a very limited number of modules (modulation index is 1.15), the proposed method still reduces the DC-link voltage ripple by 24.4% for unity power factor operation. It requires the same number of modules as the commonly utilized 3rd harmonic injection with 1/6 of the grid voltage amplitude and achieves superior results. Simulations of a 10 kV/1 MVA system confirm the analysis.
Keywords: Cascaded H-Bridge; Solid-State Transformer; Capacitor voltage ripple; Zero sequence voltage; Third harmonic injection

Fade-Over Strategy for use of Model Predictive Direct Self-Control with Field-Oriented Control - Pena, Mario; Meyer, Michael; Wallscheid, Oliver; Böcker, Joachim (2023 IEEE International Electric Machines and Drives Conference (IEMDC))

Review on: Christos Tsakas: Post-war Greco-German Relations, 1953-1981. Economic Development, Business Interests and European Integration, Basingstoke 2022. - Schönhärl, Korinna (Sehepunkte)

Plant-based dietary patterns and cardiometabolic risk factors in subgroups of individuals with diabetes - Weber, Katharina S.; Schlesinger, Sabrina; Lang, Alexander; Straßburger, Klaus; Maalmi, Haifa; Zaharia, Oana P.; Goletzke, Janina; Buyken, Anette; Trenkamp, Sandra; Wagner, Robert; Lieb, Wolfgang; Roden, Michael; et al. (Diabetologie und Stoffwechsel)

ABHÄNGEN - Ein- und Ausgrenzen, Kanonisieren, Kollaborieren in Pop, Kunst und Medien. - Jacke, Christoph (Impulse. Texte und Bilder zur Kunstvermittlung.)

Editorial. - Jacke, Christoph; Autsch, Sabine; Pickartz, Tim (Impulse. Texte und Bilder zur Kunstvermittlung.)

Zuweisung verteilter Speicher unter Maximierung der minimalen gewichteten Bandbreite - Decking, Leo
Bei dem betrachteten Speicherproblem werden Daten mit verschiedenen Zugriffswahrscheinlichkeiten auf Speicher mit verschiedenen Bandbreiten und Kapazitäten aufgeteilt, dabei sind Replikate erlaubt. Es wird die nach Zugriffswahrscheinlichkeit gewichtete kleinste Bandbreite der Daten maximiert. Wir zeigen, dass sowohl das diskrete Speicherproblem, bei dem die Bandbreite der Speicher jeweils gleichmäßig auf die dort abgelegten Daten aufgeteilt wird, als auch das kontinuierliche Speicherproblem, bei dem die Bandbreite der Speicher beliebig auf abgelegte Daten verteilt werden darf, NP-schwer ist. Es können also, wenn P ̸ = NP, keine effizienten Algorithmen für eine optimale Lösung existieren. Stattdessen zeigen wir jeweils einen 1/2-Approximationsalgorithmus.

On the Integration of Sampling Rate Synchronization and Acoustic Beamforming - Gburrek, Tobias; Schmalenstroeer, Joerg; Haeb-Umbach, Reinhold (European Signal Processing Conference (EUSIPCO))

Nietzsche’s Search for Philosophy: On the Middle Writings Keith Ansell-Pearson - Corall, Niklas (The Agonist)
In Nietzsche’s Search for Philosophy – On the Middle Writings, Keith Ansell Pearson directs his interpretive gaze to the middle writings of Nietzsche’s oeuvre, namely Human, All Too Human (HAH), Dawn and The Gay Science (GS). While at least in German Nietzsche scholarship, it is rather debatable whether or not the middle writings should have been considered “neglected”– with perhaps Dawn being a reasonable exception – it is important to read them as more than merely a detour from the “real Nietzsche” found in the Birth of Tragedy and then the late works. While Ansell-Pearson does not presume a homogeneous philosophical approach in the middle works, he characterizes the period as a whole and each work in itself as containing important aspects of Nietzsche’s “search for philosophy”, especially in consideration of Nietzsche’s attempts to “unify thought and life” (4) in what is labelled a “‘philosophical life’” (4).
Keywords: Ocean Engineering

Digitale Bruchstücke zwischen Faktalismus und Zukunftsnarration: Der Letzte Mensch und Algorithmische Regime - Corall, Niklas (Nietzsche, die Medien und die Künste im Zeitalter der Digitalisierung)

Digitizing Processes in Manufacturing Companies via Low-Code Software (to appear) - Weidmann, Nils; Kirchhoff, Jonas; Sauer, Stefan
Low-code development platforms (LCDPs) recently sparked interest in both academia and industry, promising to speed up software development and make it accessible to users with little or no programming experience. Thus, the mass-development of software applications that are custom-made to the tasks, skills, and preferences of end users is potentially enabled. Although different LCDPs have been analysed with respect to their functionality and applied to exemplary case studies in recent work, there is a shortage of experience reports in which LCDPs are used to digitize business processes in small and medium manufacturing enterprises. In this paper, we therefore summarize our experience from supporting industry partners to identify business processes that are suitable for being implemented with low-code technologies and to select an LCDP that meets the requirements of the business process while aligning with the overall digitization strategy of the respective company. We also present the opportunities and challenges of the low-code approach as perceived by industry partners. In summary, the low-code approach should be seen as an essential factor for the digitization of business processes in small and medium manufacturing companies.

Knowledge Transfer Concepts for Microgrids Sustainability - The Case of East Africa - Bogere, Paul; Temmen, Katrin; Bode, Henrik (2023 IEEE Global Engineering Education Conference (EDUCON))